On the periodic structure of the antitriangular maps on the unit square - Balibrea Gallego, Francisco; Bas, Antonio Linero (Annales Mathematicae Silesianae, 1999)
In this paper we study the periodic structure of the antitriangular maps on I2 = [0,l]×[0,l] and obtain an ordering on the periods of these maps of a Sarkovskii type.